Citizen Participation and Community Crime Prevention, 1979: Chicago Metropolitan Area Survey - Lavrakas, Paul J. ([Verlag nicht ermittelbar], 1984)
This survey was conducted as part of the Citizen Participation and Community Crime Prevention project at the Center for Urban Affairs and Policy Research, Northwestern University. The project was conducted to gain a deeper understanding of the wide range of activities in which the American public engages to be secure from crime. In particular, this survey was designed to identify the scope of anti-crime activities and investigate the processes that facilitate or inhibit the public's involvement in those activities. The geographical area for the survey was defined by the "commuting basin" of Chicago, excluding several independent cities and their suburbs (e.g., Aurora, Waukegan, and Joliet) on the northern and western fringes of that area, and excluding all areas in Indiana. Interviewing was carried out by the Survey Research Laboratory at the University of Illinois during June through August 1979. Information was gathered on people's opinions toward safety, their involvement with crime prevention activities, and the quality of life in their neighborhoods. In addition, data were assembled from Census Bureau and police reports for each community area in which respondents lived in the years immediately preceding the survey.